Identification and uses of spices in Eku market of Ethiope East Local Government area, Delta State, Nigeria: Uses of spices in Delta State of Nigeria - Ogeh, Kesiena T; Ohwo, Oghenekevwe A; Ekokogbe, Otega O (Journal of Spices and Aromatic Crops, 2025)
The research was conducted to identify spices and their uses; sourcing of spices in Eku market. Thirty spices sellers were purposively selected based on the number and quantity of spices sold. Questionnaires were administered to the selected spices sellers to gather information on socio-economic characteristics of spices sellers, uses of spices and sourcing of spices. Descriptive statistics was used to analyse the data. The result signify that the spices sellers are women, with age bracket of 45-54 years (46.7%) and are married (70%) with primary education (60%). Most of them are native of Eku community (83.3%) and have lived in the community for 41-50 years and above (36.7%). The number per house of the spices sellers are 6-10. Their main occupation is trading with an average income of N 35,000 (US$ 34) derived from the selling of spices per market day. Eleven spices were identified with their local and botanical names. The spices are used mainly as condiments in cooking different delicacies. Forty percent of the spices are used as medicine. Twenty percent are used traditionally in sacrifices and as incense by traditional worshippers. The spices are sourced from different markets within Delta State and from the Western side of the country. The spices and their usage are well known and are important to the peoples’ well being and health.